Use ClickOnce to deploy Windows applications - Lee, Wei-Meng (O'Reilly short cuts., 2006)
ClickOnce, a new technology in Visual Studio 2005, lets you quickly and easily deploy your Windows apps via web servers, file servers, or even CDs. But while ClickOnce delivers web-style deployment of your application, that's only part of the story. Once you've installed an application using ClickOnce, it can automatically check for new updates to the application, which saves time in application maintenance and upgrades. And on the security front, a ClickOnce application runs within a secure sandbox and you configure it using the Code Access Security model. So, how can you take advantage of this new technology? In this step-by-step guide to using ClickOnce, you'll learn how to create an application in Visual Studio 2005 and how to use ClickOnce to quickly get it in the hands of your customers. You'll also learn how to add security to your distributions using Code Access Security; how to update COM files without corrupting DLLs; and more. Download this PDF today for just 7.99 and discover how deploying your Windows app is just a click away.